Iron and zinc micronutrients and soil inoculation of Trichoderma harzianum enhance wheat grain quality and yield - Ali, Iftikhar; Khan, Ajab; Ali, Ahmad; Ullah, Zahid; Dai, Dong-Qin; Khan, Naveed; Khan, Asif; Al-Tawaha, Abdel Rahman; Sher, Hassan (Frontiers in Plant Science, 2022)
Malnutrition is mainly caused by iron and zinc micronutrients deficiencies affecting about half of the world’s population across the globe. To overcome malnutrition, biofortification of staple crop is the right approach to enhance nutrient contents in human daily food. This study was aimed to evaluate the role of foliar application of iron and zinc in Trichoderma harzianum treated soil on various growth characteristics, quality, and yield of wheat varieties. Plants were examined in the absence/presence of T. harzianum, and iron and zinc micronutrients in both optimal and high (stress) conditions. Although the symbiotic association of T. harzianum and common wheat being utilized as an effective approach for wheat improvement because of the dynamic growth promoting ability of the fungus, this association was found tremendously effective in the presence of foliar feeding of micronutrients for the enhancement of various growth parameters and quality of wheat. The utilization of this approach positively increased various growth parameters including spike length, grain mass, biomass, harvest index and photosynthetic pigments. The beneficial role of T. harzianum in combination with zinc and iron in stimulating plant growth and its positive impact on the intensities of HMW-GS alleles makes it an interesting approach for application in ecofriendly agricultural systems. Further, this study suggests the possible alternative way that does not merely enhance the wheat yield but can also enhance wheat quality through proper biofortification of iron and zinc to fulfil daily needs of micronutrients in staple food.